Analisis Sharing Data Wemos D1 R32 Menggunakan Web - Ardha Maliki; Joni Warta; Rafika Sari (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
The advancement of technology has increased the demand for media file storage. One common storage system used today involves the use of cables or devices that need to be connected to other devices. However, this method is not efficient for simultaneous file sharing, especially when many people want to access the same files. This research utilizes the Naive Bayes algorithm and Quality of Service method for testing and SPI (Serial Peripheral Interface) as the serial communication on Wemos D1 R32 with its sensors, in order to address this issue. The research is conducted through stages of literature review, design, testing, implementation, and testing using Wemos D1 R32 as the main platform along with supporting components such as a micro SD card reader module, an LCD OLED display, a micro SD card, and a battery. In the testing phase, conducted three times with each tested file format using the Naive Bayes algorithm in our system, the evaluation results are as follows: Very Good 86.66%, Good 13.33%, Moderate 0%, and Poor 0%.